The Inter-American System's Recent Contributions to the Development of Women's Human Rights Standards - Duhaime, Bernard; Tapias Torrado, Nancy (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2022)
This article seeks to provide an overview of some of the Inter-American Human Rights System's contributions to the development of regional legal standards on girls’ and women’s human rights from a positivist perspective. It first addresses the System’s normative and institutional framework on this topic. It then presents key jurisprudential advances in three specific areas: the right to equality and non-discrimination; the right to be free from violence; and sexual and reproductive rights.